2015
DOI: 10.1155/2015/763617
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Visible Upconversion Emission in Y2O3:Er3+‐Yb3+ by Addition of Thiourea and LiOH in the Phosphor Synthesis

Abstract: Spherical like Y2O3nanostructures doped with Er3+and Yb3+ions have been synthesized by a facile hydrothermal method. The samples were prepared by using different precipitant agents in the synthesis process. The phosphors were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and photoluminescence spectroscopy. Effects of the precipitant agents on structural, morphological, and photoluminescence properties of Y2O3:Er3+-Yb3+are studied and discussed. XRD analysis indicates that all sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…All four samples had broad bands around 3500, 1502, and 1402 cm −1 corresponding to the OH [ν(OH) group], C=O [ν(C=O) group], and CH 3 [ν(CH 3 ) group] stretching vibrations, respectively. [ 12,14,33 ] It was concluded that the bonds related to the ν(OH) group originated from H 2 O, whereas the ν(C=O) and ν(CH 3 ) groups originated from the Y(acac) 3 precursor. Interestingly, sample C, which was fabricated with H 2 O support only, showed the lowest absorbance intensity originated from the ν(O–H), ν(C=O), and ν(CH 3 ) bonds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All four samples had broad bands around 3500, 1502, and 1402 cm −1 corresponding to the OH [ν(OH) group], C=O [ν(C=O) group], and CH 3 [ν(CH 3 ) group] stretching vibrations, respectively. [ 12,14,33 ] It was concluded that the bonds related to the ν(OH) group originated from H 2 O, whereas the ν(C=O) and ν(CH 3 ) groups originated from the Y(acac) 3 precursor. Interestingly, sample C, which was fabricated with H 2 O support only, showed the lowest absorbance intensity originated from the ν(O–H), ν(C=O), and ν(CH 3 ) bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The yttrium oxide (Y 2 O 3 ) thin film has obtained significant attention due to its excellent properties, such as high dielectric constant (14)(15)(16)(17)(18)(19)(20), large bandgap (%5.5 eV), relatively high refractive index (1.7-1.9), low absorption (from near-UV to IR region), and high melting point (%2439 C). [1][2][3][4] These characteristics make Y 2 O 3 a promising material in the fields of microelectronics, waveguide, ferroelectrics, and superconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of Y 2 O 3 microspheres has drawn intensive interests in recent years. Several approaches such as hydrothermal method, [ 1 ] combustion method, [ 2 ] spray pyrolysis method, [ 3 ] precipitation method, [ 4 ] microwave assisted synthesis methods, [ 5 ] and sol–gel method [ 6 ] were employed to synthesize spherical Y 2 O 3 . However, some drawbacks such as the agglomeration, nonuniform size distribution, or uncontrollable particle size of obtained Y 2 O 3 microspheres still are the challenges for engineers and researchers.…”
Section: Introductionmentioning
confidence: 99%